Anti-Corruption Provisions in International Investment Agreements: Investor Obligations, Sustainability Considerations, and Symmetric Balance. (18th December 2020) - Yan, Yueming
ABSTRACT: Incorporating anti-corruption provisions into international investment agreements is a vital step for governments to address transnational corruption in international investment. This empirical study analyses a category of anti-corruption provisions that fosters compliance by investors. These anti-corruption provisions address anti-corruption issues either within corporate social responsibility clauses or through 'carve-out' statements. The former encourages investors to voluntarily comply with corporate social responsibility, including anti-corruption commitments, while the latter imposes direct obligations on investors by denying substantive treaty protection or access to arbitration if their investments were obtained through corruption. However, these provisions are unsatisfactory in terms of achieving their intended objectives: promoting sustainable development and achieving a symmetrical balance between investors and states. This paper addresses two central weaknesses of anti-corruption provisions. First, corporate social responsibility-based anti-corruption provisions are soft law norms that result in limited obligations or effects. Second, 'carve-out' anti-corruption provisions actually favour states' interests, because they solely evaluate investors' conduct without considering a state's corrupt act. This paper recommends that, in addition to promoting responsible and corruption-free investments on the investor side, states should commit to take necessary measures to promote the integrity of public officials, establish cooperation and improve anti-corruption standards, and preserve sufficient remedial measures for investors in cases of solicitation by state officials.